EFFECT OF EDUCATION AND CAREER DEVELOPMENT WORK PERFORMANCE OF EMPLOYEES PT. TRAIN INDONESIA (Persero) DIVISION II REGIONAL WEST SUMATRA - MARINAWATI AMOI; RAMADHANIA RAMADHANIA; LENNY HASAN (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
This study aims to influence education and work performance on the career development of employees of PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatra.The population in this study were all employees of the office environment PT. Kereta Api Indonesia (Persero) West Sumatra Regional Division II numbering 70 employees.Teknik sampling used in this study is total sampling, The data analysis used is multiple linear regression analysis. Based on the results of the research found results of multiple regression analysis is Y = 0,107 + 0,272 X1 + 0,718 X2 + e, then t-test education variable positive and significant impact on the career development of employees of PT. Kereta Api Indonesia significant value 0,027 < 0,05. Work performance variables positive effect on the career development of employees of PT. Kereta Api Indonesia with significant value 0,000 < 0,05, F-test education variable and performance together have a significant effect on the career development of employees of PT. Kereta Api Indonesia with a significant level of 0,000 < 0,005, Based on the results obtained by the coefficient of determination contained in the value of Adjusted R Square with 0,568. This means that the ability of independent variables in explaining the dependent variable is equal to 56,8% is 43,2% explained by other variables which are not addressed in this study was the exposure, networking, loyalty to the organization, coaches and sponsors, the opportunity to grow.